A 6-day stage race decreases haematocrit in male cyclists - Boston, T.; Martin, D.; McLean, B.; Lee, H.; Bannan, S.; Craig, N.; Gore, C.; Hahn, A. (1998)
The data show that a 16% plasma volume expansion can occur during a six-day stage race in nationally competitive male road cyclists. The plasma volume expansion causes morning Hct to be reduced by approximately 3.5%. Over the last three days of racing albumin concentration significantly decreased whereas plasma volume increased suggesting that mechanisms apart from albumin enrichment were responsible for the observed fluid shifts. Professional cyclists with naturally high haematocrits are more likely to exceed the UCI 50% Hct limit at the beginning, compared to the end of a stage race.